Characterization and partial envelope gene sequence of an endogenous boid retrovirus - Hassan, Roslina (2013)
Inclusion body disease (IBD) is a worldwidely prevalent and highly fatal disease of boids (Boinae and Phytoninae) believed to be caused by a retrovirus. The possibility of horizontal transmission within species has occurred likely to be mediated by the envelope (env) gene of the virus. In Malaysia, most cases of boid IBD were diagnosed based on histology and no documentation was made on the characteristics of the retrovirus. Thus, this forms the basis of this study to characterize and partially sequence the endogenous retrovirus isolated from cases of IBD in Malaysia. The isolated endogenous boid retrovirus was propagated in Vero cells systems, purified, amplified and envelope gene was sequenced to characterize the isolate. Attempt to propagate the virus in Vero systems was successful with the formation of cytopathic effect (CPE). The pool propagated supernatant was purified using continuous sucrose gradient (20-50% density gradient) technique. Following ultracentrifugation, two thick bands at sucrose density of 25% and 35% sucrose density were procured. A faint band of 45% sucrose density was also visible. The purified virus was further analyzed by electron micrographs examination, buoyant density, SDS-PAGE and western blotting. Retrovirus characteristic has been classified according to the viral tropism formation, buoyant density of 1.15g/ml-1.17g/ml, and protein pattern analysis. Electrophoresis analysis of the purified virus by SDS-PAGE showed significant differences of protein migration pattern compared from filtered ground tissues and filtered Vero supernatant sample. However, through western blotting analysis there was consistent presence of main protein band of 68 kDa in all samples which was believed that this main protein was associated with IBD. Further characteristics of the env gene encoding the SU and TM protein was amplified, purified and sequenced. The envelope sequence was compared among a series of envelope gene retrovirus using multiple sequence alignment program. The virus phylogenetic relationship classified the boid snakes in their own group. However, sequence analysis of env gene revealed 30%-40% homology to other species. Further studies should be conducted to verify the pathogenicity of the isolated virus via Koch’s postulate.